Familial spontaneous pneumothorax and Machado–Joseph disease. Issue 9 (22nd September 2020) - Pelayo, Jerald; Rau, Naraharisetty; Lo, Kevin Bryan; Azmaiparashvili, Zurab
ABSTRACT: We report the first known case of a 42-year-old man diagnosed with spinocerebellar ataxia type 3, also known as Machado–Joseph disease (MJD), who presented with recurrent spontaneous pneumothorax. Six other family members affected with MJD died of the same pulmonary complication. To date, there has been no direct genetic linkage between MJD and familial spontaneous pneumothorax. However, the mutated ataxin-3 (ATXN3) gene in MJD and Serpin Family A Member 1 (SERPINA1) gene in hereditary emphysema share the same loci on chromosome 14q32.1, which is suggestive of genetic proclivity of patients with MJD to develop familial pneumothorax. Furthermore, the abnormal ataxin protein encoded by ATXN3 and the patient's smoking history could have potentiated the dysregulation of the ubiquitin-proteasome system further aggravating his genetic predisposition to develop recurrent pneumothorax. These unexplored areas of inquiry invoke further molecular characterization to give an accent to medical knowledge as well as guide novel therapies in the future.